A censura e o princípio da neutralidade de conteúdo: liberdade de expressão e democracia - Galuppo, Marcelo Campos (2020)
The relations between society and the state reflect the relations between authority and the press. In the authoritarian philosophical postulates can be found the systematization of censorship based on the point of view of power (crown, church and government). Censorship is historically manifested by the need for prior authorization for the press activity, or by the need for individual prior authorization for the wide distribution of a speech, or for judicial prosecution of dissenting ideas, or indirect taxation of the activity of expression. The transition to libertarian postulates has brought about a reinterpretation of the relationship between authority, society and the press,attracting to the individual and the press the responsibility and the right to search for "truth", which relativizes the position of the people against authority. The function of the press ceases to be to serve the authority and happens to be to check its activity. The state that is governed by more liberal than authoritarian postulates must guarantee freedom of expression and of the press by law. To do this, it must adopt a general principle of neutrality, preventing illegitimate censorship based on the authority's point of view, especially guaranteeing freedom for the ideas he hates.